Clinical Characteristics, Intraoperative Findings, and Surgical Outcomes of Canalicular Laceration Repair with Monocanalicular Stent in Asia - Chun-Hsien Lin; Chun-Yuan Wang; Ying-Cheng Shen; Li-Chen Wei (Journal of Ophthalmology)
Purpose. To report the epidemiological and clinical data as well as surgical outcomes of canalicular lacerations with Mini-Monoka insertion at a tertiary center in Taiwan and to discuss differences in traumatic pattern, pathogenesis, and surgical outcomes between Taiwan and other countries. Methods. From 2009 to 2018, all 48 patients who underwent canalicular laceration repair with Mini-Monoka stent at a tertiary center in Taiwan were retrospectively analyzed. Demographic and clinical data and surgical outcomes were recorded. Results. The mean age of the 48 patients was 38 years. Single lower canaliculus was involved in 37 (77.1%) patients, upper canaliculus in 10 (20.8%) patients, and both in 1 (2.1%) patient. The most common etiology was motorcycle accident (41.7%), and all traffic accident injuries accounted for 68.75% of cases. Subgroup classification revealed 64.6% of patients (n=31) were categorized in the deep laceration group, and lower anatomical and functional outcomes were noted in deep laceration. The mean follow-up time was 14.5 months. Overall, the anatomical success rate was 87.5%, and the functional success rate was 91.7% after stent removal. Conclusion. Canalicular laceration caused by traffic accidents occurred with a relatively high frequency in Taiwan. Affected patients tended to be middle-aged, and deep laceration accounted for 64.6% of patients. These were contributed by the avulsive eyelid injury mechanism caused by traffic accidents. Furthermore, the deeper lacerated site was located, and the lower anatomical and functional success rates were observed. Early repair after trauma with Mini-Monoka stents achieved good eyelid position (100%) as well as good anatomical (87.5%) and functional (91.7%) success without serious complication.